EVALUATION OF QOL AND OUTCOMES OF PATIENTS WITH NEOPLASIA UNDERGOING COLECTOMY - MUMTAZ, S; HAIDER, ANH (Biological and Clinical Sciences Research Journal, 2024)
Colectomy is a common surgical intervention for colonic neoplasia and complex colonic polyps. While it is effective in treating the underlying condition, it can significantly impact bowel function and quality of life, both in the short and long term. Objective: To assess the short-term and long-term quality of life and functional outcomes of colectomy in patients with neoplasia. Methods: A prospective study was conducted in the General Surgery Department of General Hospital, Lahore from September 2023 to September 2024. A total of 100 patients undergoing or had undergone hemicolectomy or colectomy were included in the study. Patients were divided into two groups based on the timing of colectomy. Early bowel function was assessed in 50 patients with benign complex colonic polyps undergoing colectomy. Intermediate bowel function was assessed in patients who had undergone colectomy for neoplasia 2-4 years before the study. A group of 50 healthy immediate relatives of patients was included as the control group for evaluating early bowel function. Postoperative bowel function was assessed by Memorial Sloan-Kettering Cancer Centre questionnaire and the EuroQoL questionnaire was used to measure quality of life. Results: Six-months and one-year post-op, patients had increased frequency of bowel movement per day (p<0.001). Lower frequency score, reduced gas control and differentiation between gas and stool one year after surgery were significant, indicating worse function. A weak association between EuroQol visual analog score and six months post-op urgency score (p=0.006), flatulence control (p=0.004), and total MSKCC score (p=0.005), hence patients with higher scores had good quality of life. Conclusion: Colectomy adversely impacts bowel function up to 1 year after surgery, however, it is comparable to the general population.